A Particle System with Explosions: Law of Large Numbers for the Density of Particles and the Blow-Up Time - Tertuliano, Franco (2012)
Consider a system of independent random walks in the discrete torus with creation-annihilation of particles and possible explosion of the total number of particles in finite time. Rescaling space and rates for diffusion/creation/annihilation of particles, we obtain a stong law of large numbers for the density of particles in the supremum norm. The limiting object is a classical solution to the semilinear heat equation ∂tu = ∂xxu + f(u). If f(u) = u p , 1 < p ≤ 3, we also obtain a law of large numbers for the explosion time.